2016
DOI: 10.1136/jclinpath-2016-203754
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 expression is associated with tumour immunity and prognosis in gingival squamous cell carcinoma

Abstract: These findings suggest that Gal-1 plays an important role in immune escape of GSCC cells, and Gal-1 expression level may be a useful clinicopathological prognostic marker for GSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
(45 reference statements)
0
22
0
1
Order By: Relevance
“…EPHA2 has been previously identified as a highly expressed surface protein in OS cells and tissue [41][42][43] . We found that LGALS1, a potent inducer of T-cell apoptosis 44,45 , was LGALS1 upregulation has been reported in human OS tissue samples 46 and is associated with metastatic and aggressive cancer cell phenotypes [47][48][49] . Hypoxia stimulated the MHC class I assembly based on upregulation of PSA 50 , PSMD 51 , and HLA-A/B.…”
Section: Figure 5 Prm-based Confirmation Of Hypoxia-induced Expressimentioning
confidence: 66%
“…EPHA2 has been previously identified as a highly expressed surface protein in OS cells and tissue [41][42][43] . We found that LGALS1, a potent inducer of T-cell apoptosis 44,45 , was LGALS1 upregulation has been reported in human OS tissue samples 46 and is associated with metastatic and aggressive cancer cell phenotypes [47][48][49] . Hypoxia stimulated the MHC class I assembly based on upregulation of PSA 50 , PSMD 51 , and HLA-A/B.…”
Section: Figure 5 Prm-based Confirmation Of Hypoxia-induced Expressimentioning
confidence: 66%
“…Based on their findings, these authors suggested that Gal 1 may represent a novel molecular target for the diagnosis and prognosis of oral SCCs, and that its inhibitors might be useful in the management of early-stage oral carcinogenesis. More recently Noda et al (41) determined that Gal 1 expression in gingival SCC significantly correlates with the histological differentiation of tumor cells, the extent of apoptosis and T cell infiltration, lymph node metastasis, and overall survival rate. Based on their findings, these authors suggested that this galectin may be used as a clinicopathological prognostic marker for gingival SCC.…”
Section: α Epithelialmentioning
confidence: 99%
“…Galectins play important roles in the development of acute inflammation as well as chronic inflammation (27). Both galectin (Gal)-1 and Gal-3 are distributed widely in different cells and tissue types, including innate and adaptive immune cells (23,28). Gal-1 and Gal-3 facilitate the proliferation of hepatic stellate cells (HSCs) and play an important role in liver fibrosis (29).…”
Section: Introductionmentioning
confidence: 99%